Utilizing Supervision Power by the “Dewan Perwakilan Rakyat Daerah” in Government Fighting Pandemic Covid-19: A Case Study Blitar Regency - Lala Amelinda Fatin; Asep Nurjaman (Jurnal Studi Sosial dan Politik, 2022)
This study aims to explore the role of the Blitar Regency DPRD in improving the succession of handling Covid-19 through supervision. This research uses descriptive research with a qualitative approach. Data collection techniques were done through interviews, observation, and documentation. This study focuses on explaining the role of the Blitar Regency DPRD in supervising over the handling of the Covid-19 pandemic. The DPRD’s oversight in handling the COVID-19 pandemic is an important factor to oversee the activities of the Regional Government and to minimize the problems found in handling the COVID-19 pandemic. The results of the study showed that the Blitar Regency DPRD in improving the succession of handling the COVID-19 pandemic has carried out toward intense supervision. The supervision was done both directly and indirectly. Covid-19 cases in Blitar Regency continued to experience a significant decline from September to December. Thus, it can be concluded that the Blitar Regency DPRD plays a major role in the successful handling of the pandemic through supervision. This shows that the DPRD as an institution that functions to monitor the public’s activities by the government plays a very important role to apply the policies. Therefore, the DPRD and the Regional Government need to make good synergies and coordination so that the government in Indonesia runs well.